PENGOLAHAN DATA SENSUS PENDUDUK MENGGUNAKAN BAHASA PEMROGRAMAN PHP BERBASIS WEB PADA KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - Erlinda Erlinda (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2018)
Based on research conducted at the Bukit Sundi District Office Solok District shows important information and news for the community, especially information on population census and other information. By looking at the current technological sophistication, the right internet technology, which has website facilities, with accuracy both in terms of time and cost and information that can be accessed at any time, the author will use it by building a website using the PHP application, to provide accurate and fast information, which we can provide to gather more up-to-date information.